2013
DOI: 10.1080/09712119.2013.822804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of castration and zeranol on fatty acid composition and cholesterol content of hair lamb meat

Abstract: Hair lambs (n 072, crosses of Blackbelly, Dorper, and Katahdin breeds) with an average age of 90 days (21.49 2.3 kg of BW) were used to investigate the effects of sex class (CLASS: ram vs. wether) and zeranol implant (IMP: control vs. 12 mg) on fat and cholesterol content, and fatty acids (FAs) composition of intramuscular longissimus dorsi (LD) and biceps femoris (BF) and subcutaneous fat (SBC) depots of the loin area. Animals were assigned to one of four treatments with a factorial arrangement (n 018): (1) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Additionally, Santos-Silva et al (2002) showed that the proportion of CLA present in intramuscular fat was dependent on feeding system. While some researchers reported that CLA rates are higher than the rates found in this study (Garcia et al, 2008;Cieslak et al, 2013;Villalobos-Villalobos et al, 2014), others have indicated lower CLA rate in lamb genotypes (Santos-Silva et al, 2002;Yarali et al, 2014). Linoleic acid (n-6, C18:2) predominates among the PUFAs.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…Additionally, Santos-Silva et al (2002) showed that the proportion of CLA present in intramuscular fat was dependent on feeding system. While some researchers reported that CLA rates are higher than the rates found in this study (Garcia et al, 2008;Cieslak et al, 2013;Villalobos-Villalobos et al, 2014), others have indicated lower CLA rate in lamb genotypes (Santos-Silva et al, 2002;Yarali et al, 2014). Linoleic acid (n-6, C18:2) predominates among the PUFAs.…”
Section: Resultscontrasting
confidence: 70%
“…As it is shown in Table 1, the proportion of SFAs was higher in BC lambs than the other lamb breeds and differences in the total percentage of SFAs were insignificant (p > 0.05). SFAs content in all genotypes was relatively high and similar to those notified by Villalobos-Villalobos et al (2014).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The livestock and meat industry is constantly looking for alternatives to promote fast and efficient growth of livestock, improve the carcass yield, i.e., increasing Longissimus dorsi muscle area (Beermann 2009;Etherton 2009) or diminishing the fat content in the carcass (Villalobos-Villalobos et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, isoenergetic and isonitrogenous diet is one of the important factors need to be considered when evaluating the effects of diet energy structure on YC supplementation. Moreover, given that mutton is a high‐quality source of PUFA for humans, increasing the polyunsaturated fatty acid (PUFA) content and reducing the saturated fatty acid (SFA) content of mutton is a goal that scholars need to consider (Villalobos‐Villalobos et al, ). However, few studies have been performed regarding the effects of YC on the fatty acid profile of the longissimus dorsi (LD) muscle.…”
Section: Introductionmentioning
confidence: 99%